Statistical analysis on avoidance of palindromic sequences in genomes of microorganisms - Rekašius, Tomas; Timinskas, Albertas (Lietuvos matematikos rinkinys, 2003)
The statistical analysis of oligonucleotide combinations and mathematical modelling of outgoing processes is very successfully used in the research. It present research we applied Markov chainmodel. Using themodel few new methodologies for research of oligonucleotidic composition within DNA sequenceswe created.